Formation, Reactivity, and Catalytic Behavior of a Keggin Polyoxometalate/Bipyridine Hybrid in the Epoxidation of Cyclooctene with H2O2 - Hidalgo, Gabriel; Barozzino-Consiglio, Gabriella; Robeyns, Koen; Devillers, Michel; Gaigneaux, Eric M (Inorganic chemistry, 2023)
The present study further explores the behavior of polyoxometalate-based hybrid compounds as catalysts for liquid-phase cyclooctene epoxidation with H2O2. Precisely, it unveils the nature of the relevant active species derived from the hybrid based on Keggin polyoxometalate (POM) and bipyridines (bpy) of formula (2,2'-Hbpy)3[PW12O40] (1). Whereas (i) it is generally accepted that the catalytic oxidation of organic substrates by H2O2 involving Keggin HPAs proceeds via an oxygen transfer route from a peroxo intermediate and (ii) the catalytically active peroxo species is commonly postulated to be the polyperoxotungstate {PO4[W(O)(O2)2]4}3- complex (PW4), we show that the studied epoxidation reaction seems to be more sophisticated than commonly reported. During the catalytic epoxidation, 1 underwent a partial transformation into two oxidized species, 2 and 3. Compound 3 corresponding to 2,2'-bipyridinium oxodiperoxotungstate of formula [WO(O2)2(2,2'-bpy)] was shown to be the main species responsible for the selective epoxidation of cyclooctene since 2 (in which the POM is associated with a protonated mono-N-oxide derivative of 2,2'-bpy of formula (2,2'-HbpyO)3[PW12O40]) exhibited no activity. The structures of 1, 2, and 3 were solved by single-crystal X-ray diffraction and were independently synthesized. The speciation of 1 was monitored under catalytic conditions by 1H and 1H DOSY NMR spectroscopies, where the formation in situ of 2 and 3 was revealed. A reaction mechanism is proposed that highlights the pivotal, yet often underestimated, role of H2O2 in the reached catalytic performances. The active species responsible for the oxygen transfer to cyclooctene is a hydroperoxide intermediate species that is formed by the interaction between the anionic structure of the catalyst and H2O2. The latter operates as a "conservative agent" whose presence in the catalytic system is required to prevent the catalysts from deactivating irreversibly.The present study further explores the behavior of polyoxometalate-based hybrid compounds as catalysts for liquid-phase cyclooctene epoxidation with H2O2. Precisely, it unveils the nature of the relevant active species derived from the hybrid based on Keggin polyoxometalate (POM) and bipyridines (bpy) of formula (2,2'-Hbpy)3[PW12O40] (1). Whereas (i) it is generally accepted that the catalytic oxidation of organic substrates by H2O2 involving Keggin HPAs proceeds via an oxygen transfer route from a peroxo intermediate and (ii) the catalytically active peroxo species is commonly postulated to be the polyperoxotungstate {PO4[W(O)(O2)2]4}3- complex (PW4), we show that the studied epoxidation reaction seems to be more sophisticated than commonly reported. During the catalytic epoxidation, 1 underwent a partial transformation into two oxidized species, 2 and 3. Compound 3 corresponding to 2,2'-bipyridinium oxodiperoxotungstate of formula [WO(O2)2(2,2'-bpy)] was shown to be the main species responsible for the selective epoxidation of cyclooctene since 2 (in which the POM is associated with a protonated mono-N-oxide derivative of 2,2'-bpy of formula (2,2'-HbpyO)3[PW12O40]) exhibited no activity. The structures of 1, 2, and 3 were solved by single-crystal X-ray diffraction and were independently synthesized. The speciation of 1 was monitored under catalytic conditions by 1H and 1H DOSY NMR spectroscopies, where the formation in situ of 2 and 3 was revealed. A reaction mechanism is proposed that highlights the pivotal, yet often underestimated, role of H2O2 in the reached catalytic performances. The active species responsible for the oxygen transfer to cyclooctene is a hydroperoxide intermediate species that is formed by the interaction between the anionic structure of the catalyst and H2O2. The latter operates as a "conservative agent" whose presence in the catalytic system is required to prevent the catalysts from deactivating irreversibly.